Citation and Referencing as a Catalyst for Optimizing E-Resource Utilization: The Case of Graduate Students in Christian Universities in Nairobi County - Kinoti, Dennis Mwaki; Gichohi, Paul Maku; Gatimu, Winfred (International Journal of Professional Practice, 2023)
Sophisticated systems and technologies have led to the proliferation of e-resources and their adoption alongside print media in higher learning institutions, particularly with the rise of e-learning. To ensure effective utilization of e-resources, citation and referencing competences remain integral in graduate students’ research, learning and scholastic achievement. Nonetheless, studies done reveal that e-resources remain underutilized. This study aimed at investigating the role of citation and referencing competences in enhancing e-resource utilization among graduate students in Christian Universities in Nairobi County. Descriptive survey research design was used to gather comprehensive data. Stratified and systematic sampling was employed to select graduate students, and purposive sampling to select librarians. The target population was 843 graduate students and 8 library staff. A 20% sample was selected, resulting to 168 graduate students and 8 librarians. Questionnaires collected data from graduate students and the librarians were interviewed. Thematic analysis was done for qualitative data, which was presented thematically and using verbatim. Quantitative data analysis was conducted using SPSS, employing descriptive and inferential statistical techniques. The results were presented in tables and figures. The findings revealed that graduate students showed a strong preference for and effectively utilized a variety of e-resources. Additionally, they demonstrated a satisfactory understanding and application of citation, referencing styles, and reference management software/tools. The Pearson correlation analysis indicated a strong positive linear association. Consequently, the study concluded that citing and referencing significantly affected graduate students’ use of e-resources. Based on these findings, the study recommends mandatory training in citing and referencing for graduate students in Christian universities in Nairobi County. It emphasizes the need to market e-resources, analyze usage statistics, and reassess the library budget. Additionally, attention should be given to mastering referencing, improving citation ability, and utilizing reference management tools/software in a bid to optimizing e-resource use and overall academic success.